The Islamic Ethical Leadership and Employees’ Ethical Behavior: The Moderating Role of Ethical Sensitivity - Emma Yulianti; Margono Setiawan; Surachman Surachman; Dodi Wirawan Irawanto (Universitas Hayam Wuruk Perbanas, 2020)
Previous literatures have described the influence of ethical leadership on employees’ outcomes. However, many researchers have not yet revealed the mechanism of this effect. Previous research has found that cultural and social factors influence leader-ship styles; therefore, studying ethical leadership styles in different cultural and social environments is important in order to uncover the effectiveness of ethical leadership styles. The purpose of this study was to examine how the mechanism of Islamic ethical leadership influences the behavior of professional nurses who work at the Islamic Hos-pital. There were 212 professional nurses used as the respondents in this study. The data were collected using questionnaires and processed quantitatively using Struc-tural Equation Model (SEM) - WarpPLS 5.0. The results showed that all the hypoth-eses proposed were accepted. Islamic ethical leadership is proven to have a significant influence on ethical behavior of nurses. Besides, ethical sensitivity is proven to have a significant positive effect on ethical behavior. This study also proves that ethical sensitivity moderates the influence of Islamic ethical leadership on nurses' ethical be-havior. It can be implied that ethical sensitivity is an important factor for developing employees’ ethical behavior in the workplace.